PEMBERIAN INTERVENSI WATER TEPID SPONGE DAN MANAJEMEN MUAL PADA ANAK HIPERTERMIA DAN DEFISIT NUTRISI: LAPORAN KASUS - Yuli Rahmawati Utami; Rakhmawati, Windy; Hendrawati, Sri (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
Histoplasmosis and Tuberculosis (TB) have similar clinical manifestations such as fever, weight loss, night sweats, fatigue. There is a dual diagnosis related to infections that cause febrile neutropenia and malnutrition, an emergency condition. The water tepid sponge method and nausea management need to be used. The aim of this study to determine the effect of applying water tepid sponges and management of nausea in children with hyperthermia and nutritional deficits. The Research design is a case report. The Research sample is client An. L, was diagnosed with pulmonary tuberculosis based on OAT and Histoplasmosis. The Research was carried out four days (observation, assessment, interviews, and intervention). The interventions carried out are warm compress on the forehead, water tepid sponge, combination with paracetamol, and nausea management according to the patient's condition. The evaluation was carried out before and after the intervention. After nausea management, An. L experienced an increase food portions and ate regularly. Decrease in body temperature within the normal range (36.5-37.5°C) for different durations after several interventions. Providing water tepid sponge intervention and nausea management proved effective in reducing fever and increasing appetite. Keywords: children, histoplasmosis, nausea management, pulmonary tuberculosis, water tepid sponge.